Mass Migration to Israel and Natives? Transitions from Employment - Sarit Cohen-Goldner; Marco Daniele Paserman (Institute for the Study of Labor (IZA), 2004)
This paper studies the impact of mass migration from the Former Soviet Union to Israel on natives? probability of moving from employment to non-employment in a segmented labor market that is defined by various combinations of schooling, occupation, industry, district of residence and experience. We find that the share of immigrants in a given labor market segment is generally positively associated with the probability of natives to move from employment in that segment to non-employment, both for males and females. However, when segment fixed-effects are added, this effect is substantially reduced for males, and disappears or is even reversed for females. We conclude that immigrants are negatively selected into occupations with high turnover and that natives were not facing higher probability to exit employment due to immigrants? presence in a certain occupation. Allowing the effect to vary across natives with different levels of education and experience reveals that young men, educated men and workers in the private sector are adversely affected by the presence of immigrants.
Keywords: F22; J21; J30; J00; J61; 330; immigration; labor demand; labor supply; segmented labor markets; employment transitions; Einwanderung; Arbeitsmarkt; Israel